Kemampuan Berpikir Kreatif Siswa Pada Realistic Mathematics Education (RME) - MUHAMMAD HUDA; MUHAMMAD HUDA (JURUSAN PENDIDIKAN GURU SEKOLAH DASAR, 2021)
This study aims to determine the effectiveness of the Realistic Mathematics Education model on students' creative thinking abilities. The method used is a quantitative method. The samples in this study were fourth grade students at SDN Bintoro 8 and grade IV students at SDN Bintoro 9. Quantitative data were analyzed by t-test and gain test based on the value of students' creative thinking abilities. The results showed that (1) the average difference in creative thinking abilities of experimental class students was better than the control class; (2) improvement of students' creative thinking ability in the experimental class which is higher than the control class.